Scoop - Waugh, Evelyn, 1903-1966. (London : Penguin Books, 2000)
William Boot, a quiet writer of a nature column for London's "Daily Beast" becomes the inadvertent star of British super-journalism when he is mistakenly sent to cover the war in Ishmaelia.
Adult.
Adult
Keywords: Reporters and reporting -- England -- London -- Fiction; War correspondents -- Fiction; Humorous fiction; Reporters and reporting -- Fiction; War correspondents -- Fiction